Clinical Pharmacology of Ticarcillin (α-Carboxyl-3-Thienylmethyl Penicillin, BRL-2288) - Rodriguez, Victorio (1973)
Clinical pharmacological studies of ticarcillin (α-carboxyl-3-thienylmethyl penicillin, BRL-2288) were conducted in patients with metastatic cancer and leukemia.After administration of 0.5 g intramuscularly, 1 g intramuscularly, and 1 g intravenously, the mean peak concentrations in serum were 18, 35, and 106 μg/ml, respectively. Greater than 80% of ticarcillin was excreted in the urine during the subsequent 6-h period. The mean concentrations in the serum of patients 15 min after they received an intravenous injection of 4 g of ticarcillin with and without probenecid were 508 and 519 μg/ml, respectively. Serum levels were determined in patients who received ticarcillin for therapy of infection in doses of 5 g every 6 h. The mean drug concentration in serum 15 min after the rapid administration of the first dose was 433 μg/ml. Subsequent doses were given during a 2-h infusion and the study was repeated 2 days later. The average initial serum level (4 h after the completion of the preceding dose) was 19 μg/ml, and the mean serum level at 15 min was 213 μg/ml. Drug concentrations in the serum of patients receiving ticarcillin by infusion in doses of 3.5 g every 4 h were also determined. In patients with normal renal function, the average initial serum level (2 h after completion of the preceding dose) was 49 μg/ml and the mean level at 15 min was 210 μg/ml. Drug concentrations in the serum of patients with impaired renal function were considerably higher. No detectable levels of ticarcillin were found in the cerebrospinal fluid.